Unicystic Ameloblastoma with Mural Proliferation Managed by Conservative Treatment - Natália Galvão Garcia; Denise Tostes Oliveira; Moacyr Tadeu Vicente Rodrigues (Case Reports in Pathology)
Unicystic ameloblastoma is a distinguishable entity of ameloblastomas, characterized by slow growth and being relatively locally aggressive. Three histological types are recognized according to the degree of ameloblastomatous epithelial extension, namely, luminal, intraluminal, and mural types. This classification has a direct bearing on their biological behavior, treatment, and prognosis. However, there is difficulty in determining the most appropriate form of treatment for unicystic ameloblastoma. We present a case of unicystic ameloblastoma that occurred in the right posterior mandible of 19-year-old girl, which was enucleated and did not recur after 12-month follow-up.